Bioanalysis: Heri, hodie, cras. Issue 11 (23rd April 2013) - Righetti, Pier Giorgio
Abstract : This review, compiled for celebrating the decennial of the series of issues of Electrophoresis on bioanalysis, does not cover much heri (yesterday in Latin), since this was extensively described by my previous review Electrophoresis 2004, 25, 2111–2127, nor, for that matter cras (tomorrow in Latin) since making predictions on future scenarios is decidedly a nonscientific endeavor, but is concentrated onto hodie (today in Latin). Recent progress in the following fields is covered: SDS electrophoresis; IEF and the unraveling of the chemistry and composition of soluble carrier ampholytes; 2D maps; CE with microchip technology and some coatings of unique performance; chemistry and function of combinatorial peptide ligand libraries. This latter technique is becoming fundamental in the detection and identification of low‐abundance proteins in proteome analysis.